1986
DOI: 10.1093/bja/58.12.1447
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Datex Relaxograph During Anaesthesia and Atracurium-Induced Neuromuscular Blockade

Abstract: The Datex Relaxograph is a recently introduced electromyographic monitor of neuromuscular transmission. It has been assessed in patients requiring neuromuscular blockade and the results compared with those obtained simultaneously with a force transducer. There was a good correlation between the two methods of measurement for both twitch height and train-of-four ratio (correlation coefficients 0.93 and 0.97, respectively). The Datex Relaxograph proved easy to use in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Although the results of measurements from EMG and MMG correlate well (32), these cannot be used interchangeably (33, 34). Evoked EMG records the compound muscle action potential using recording electrodes after stimulation of the corresponding nerve.…”
Section: Equipmentmentioning
confidence: 99%
“…Although the results of measurements from EMG and MMG correlate well (32), these cannot be used interchangeably (33, 34). Evoked EMG records the compound muscle action potential using recording electrodes after stimulation of the corresponding nerve.…”
Section: Equipmentmentioning
confidence: 99%
“…The data generated by the indirectly evoked EMG should be used with some understanding of its limitations as a predictor of mechanical response. Although Carter and colleagues [11] found a good correlation between the two methods of measurement for both twitch height and trainof-four ratio (correlation coefficients 0.93 and 0.97, respectively), Kopman [12] found that the simultaneously evoked (hypothenar) EMG and MMG did not give identical information. The regression line for the Tl :Tc (twitch depression/ control twitch) ratio was parallel to the line of identity, but showed an absolute offset of 15%.…”
Section: Discussionmentioning
confidence: 97%
“…After induction of anaesthesia, 30 min was allowed for stabilization, during which time Ringer's lactate 500-750 ml was administered to ensure optimal peripheral circulation. Recovery from suxamethonium block was assessed with a neuromuscular relaxation monitor (Relaxograph NMT-100 rev.01, software 3.0, Datex, Finland) [6]. No other neuromuscular blocking drug was used during the study.…”
Section: Methodsmentioning
confidence: 99%
“…curarization after operation [1,2]. In clinical anaesthesia, the evoked compound action potential (ECAP) response of the hand muscles [3][4][5][6] may be used to monitor neuromuscular block.…”
mentioning
confidence: 99%